Persistent alterations in cerebrovascular reactivity in response to hypercapnia following pediatric mild traumatic brain injury. Issue 12 (December 2020) - Dodd, Andrew B; Lu, Hanzhang; Wertz, Christopher J; Ling, Josef M; Shaff, Nicholas A; Wasserott, Benjamin C; Meier, Timothy B; Park, Grace; Oglesbee, Scott J; Phillips, John P; Campbell, Richard A; Liu, Peiying; et al.
Much attention has been paid to the effects of mild traumatic brain injury (mTBI) on cerebrovascular reactivity in adult populations, yet it remains understudied in pediatric injury. In this study, 30 adolescents (12–18 years old) with pediatric mTBI (pmTBI) and 35 age- and sex-matched healthy controls (HC) underwent clinical and neuroimaging assessments during sub-acute (6.9 ± 2.2 days) and early chronic (120.4 ± 11.7 days) phases of injury. Relative to controls, pmTBI reported greater initial post-concussion symptoms, headache, pain, and anxiety, resolving by four months post-injury. Patients reported increased sleep issues and exhibited deficits in processing speed and attention across both visits. In grey-white matter interface areas throughout the brain, pmTBI displayed increased maximal fit/amplitude of a time-shifted end-tidal CO2 regressor to blood oxygen-level dependent response relative to HC, as well as increased latency to maximal fit. The alterations persisted through the early chronic phase of injury, with maximal fit being associated with complaints of ongoing sleep disturbances during post hoc analyses but not cognitive measures of processing speed or attention. Collectively, these findings suggest that deficits in the speed and degree of cerebrovascular reactivity may persist longer than current conceptualizations about clinical recovery within 30 days.